Positive periodic solutions of a discrete mutualism model with time delays - Yongkun Li (International Journal of Mathematics and Mathematical Sciences)
A discrete periodic mutualism model with time delays is investigated. By using Gaines and Mawhin's continuation theorem of coincidence degree theory, the existence of positive periodic solutions of the model is established.